Financial wellbeing of single mothers in Penang: the sole breadwinner / Zarina Md Nor ... [et al.] - Md Nor, Zarina; Abu Hasan, Intan Shafina; Omar, Bahiyah; N Vellymalay, Suresh Kumar; Omar, Azizah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam (UiTM), 2018)
Financial hardship has been documented as one of the most common issues faced by single mothers in many parts of the world. Therefore, studies on the financial well-being of a single mother are important to undertake as it determines the living standard of their households. This study explores the financial wellbeing of divorced single mothers in the state of Penang and its impact on the livelihood of single mothers and their families. This study employs a simple qualitative method via interviews. The respondents are chosen based on their willingness to participate in the study and that they fulfill specific criteria. The interviews have been carried out with fifteen working age divorced single mothers to identify the available sources of income including salary, wages, child support and other possible financial assistance. The findings indicate that most of the single mothers encounter financial hardships in their lives. This is probably due to their low level of education attainment which is the common enabler for well-paid jobs and also based on the number of dependents in their households. Moreover, we find that only four of the respondents receive child support from the father of their children. In the midst of increasing living cost, the financial wellbeing of these single mothers is in questions and, their ability to save for the rainy days are far reaching.